Potensi Masjid Syuhada-Kota Yogyakarta Sebagai Bangunan Cagar Budaya - Laksmi Eko Safitri (Program Studi Sastra Indonesia UIN Sunan Ampel Surabaya, 2020)
This study aims to explain the potential of the Syuhada Mosque as a cultural heritage building in Yogyakarta. This study uses a qualitative research method based on a literature review on the History of the Syuhada Mosque by Kumoro (2019), Constitution Number 11 of 2010 concerning Cultural Heritage and Regional Regulations of the Special Province of Yogyakarta, especially Number 6 of 2012 concerning Preservation of Cultural Heritage and Cultural Heritage. The results of this study are (1) The history of the construction of the Mosque of Syuhada in 1950-1952 is closely related to the location and history of the struggle of Indonesia in maintaining independence after the relocation of the capital to Yogyakarta, (2) The Syuhada Mosque has the potential to be a cultural heritage building in Yogyakarta because it is in accordance with the contents of (a) Constitution Number 11 of 2010 concerning Cultural Heritage: Article 1 (number 1), Article 1 (number 3), Article 1 (number 18), and Article 5 and (b) Regional Regulation of the Special Province of Yogyakarta Number 6 of 2012 concerning Preservation of Cultural Heritage and Cultural Heritage: Article 12. Overall, it can be seen that the establishment of the Syuhada Mosque building in Yogyakarta Mayor Decree Number 297 of 2019 related to the Cultural Heritage of the City of Yogyakarta means that the status of the Syuhada Mosque as a list of the Cultural Heritage of the Special Region of Yogyakarta deserves to be upgraded to the Cultural Heritage Building.